BENDING STRENGTH OF HYBRID COMPOSITE OF GLASS AND NATURAL FIBER PHINEAGE LEAVES - Latuconsina, Muhammad Fachnoor; Priyahapsara, Istyawan (Institut Teknologi Dirgantara Adisutjipto, 2021)
The development of composite fibers has developed very much, and to reduce the environmental impact, composite fibers use natural fiber alternatives. The development of composite fibers has developed very much, and to reduce the environmental impact, composite fibers use natural fiber alternatives. One of the natural fibers that are commonly used is natural fiber from pineapple leaves, where natural fiber from ananas leaves is still very minimal in its commercial use and is only considered as waste